English Students' Difficulties with Parallel Structure in the Structure and Written Expression Section in TOEFL Test - Annisa Purnama Sari; Witri Oktavia (Universitas Negeri Padang, 2023)
The purpose of this study was to investigate English students' difficulties with parallel structure in the TOEFL test. Descriptive research with a quantitative approach is used in this study. The subject of this research was English education students at Universitas Negeri Padang in the 2019 academic year. To collect data, the researcher conducted a grammar test. In this study, the data were analyzed in several steps, including classifying student responses as correct or incorrect, calculating student test scores, calculating the percentage of difficulty in each skill, and determining the level of difficulty in each question. The test result shows that the students face difficulties in answering TOEFL questions related to parallel structure in the structure and written expression section. It can be seen in the average student test score, which is 56. Parallel structure with comparison is the most difficult skill with a percentage of 46.3%. On top of that, skills related to parallel structure with coordinate conjunctions get a percentage of student difficulty of 45.6%, while skills related to parallel structure with paired conjunctions get a percentage of student difficulty of 41%. Based on the results of calculating the difficulty level of the questions, there are 2 questions in the difficult category, 21 questions in the medium category, and 7 questions in the easy category.